The professionalism of vocational high school supervisors: a study of qualitative analysis - Tasrif, Elfi (International Journal of Research in Counseling and Education, 2021)
Supervisors carry out educational supervision to develop a better quality learning environment, including vocational high schools (VHS). This research is qualitative research with a case study research design. The main target of the research is VHS supervisors in Padang City. This research is limited to describing the professionalism of supervisors qualitatively. The data sources of this research were crucial informants, who were determined purposively. Data collection techniques with interview and observation techniques. Data analysis by collecting data, coding, linking, and interpreting themes. The results showed that the professionalism of VHS supervisors in carrying out their duties is still not following the quality standards of supervisors. The conclusion is that the supervisor's low professionalism is indicated by the supervisor's low motivation, lack of pride in his profession as a supervisor, the supervisor is not independent, and the supervisor's verbal communication is not good.